What’s Wrong with SISDALSKRIPSI? An Evaluation of the Thesis Control System at UNNES - ., Kardoyo; Nurkhin, A; ., Muhsin; Pramusinto, H (KnE Social Sciences, 2018)
This study aims to examine the implementation of thesis control system (SISDALSKRIPSI) at the Faculty of Economics, Universitas Negeri Semarang (FE UNNES). The concept of Unified Theory of Acceptance and Use of Technology (UTAUT) is used to understand the factors that influence the students want to use SISDALSKRIPSI in FE UNNES. The research design is evaluative research. The population of the research is the students of the Department of Economic Education, FE UNNES who are preparing the thesis. Respondents in this study are also lecturers and supervisors at FE UNNES. The questionnaires and interviews were used to collect the data. Data analysis techniques used are multiple regression analysis and focus group discussion. The results showed that effort expectancy, performance expectancy, and social influence have positive and significant impact on intention to use SISDALSKRIPSI. Intension and facilitating condition also proved to have positive and significant effect on the actual use of SISDALSKRIPSI. Other results indicate that SISDALSKRIPSI still have to be improved. So it will be easier to use by lecturers and students. Keywords: on time graduation; SISDALSKRIPSI; thesis control system; UTAUT